О РУДНОЙ ПЕТРОФИЗИКЕ - Ващилов Ю.Я. (My University, 2007)
Discussing the article «Spatial and Genetic Relationships Between the Areas of Anomalous Petrophysical Characteristics, Ore Mineralization and a Deep High-Conductive Subvertical Zone within the Natalka Lode Area» by V. M. Sharafutdinov and I. M. Khasanov, in: Вестник СВНЦ ДВО РАН, № 4, 2006, с. 2-11.
Keywords: 552:553